2022
DOI: 10.1101/2022.08.22.504761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary determinants of reproductive seasonality: a theoretical approach

Abstract: Reproductive seasonality is a major adaptation to seasonal cycles and varies substantially among organisms. This variation, which was long thought to reflect a simple latitudinal gradient, remains poorly understood for many species, in part due to a lacunary theoretical framework. Because seasonal cycles are increasingly disrupted by climate change, a better understanding of the ecology of reproductive seasonality could generate important insights on how climate change may affect biodiversity. The goal of this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 80 publications
1
4
1
Order By: Relevance
“…Two recent studies found no or little effect of climatic unpredictability on the intensity of reproductive seasonality at the population level, one in chacma baboons (Dezeure et al, 2023) and one on yellow baboons using a modelling approach (Burtschell et al, 2023), questioning the robustness of the effect found in this study. This discrepancy may come from the fact that unpredictable climates select for reproductive flexibility, rather than nonseasonal breeding.…”
Section: Environmental Unpredictability May Drive Flexible Reproducti...contrasting
confidence: 58%
See 4 more Smart Citations
“…Two recent studies found no or little effect of climatic unpredictability on the intensity of reproductive seasonality at the population level, one in chacma baboons (Dezeure et al, 2023) and one on yellow baboons using a modelling approach (Burtschell et al, 2023), questioning the robustness of the effect found in this study. This discrepancy may come from the fact that unpredictable climates select for reproductive flexibility, rather than nonseasonal breeding.…”
Section: Environmental Unpredictability May Drive Flexible Reproducti...contrasting
confidence: 58%
“…While English et al (2012) found that higher inter-annual variation in food availability decreased the intensity of birth synchrony across 38 ungulate species, two studies of red deer, Cervus elaphus L. (Loe et al, 2005) and chacma baboons, Papio ursinus (Dezeure et al, 2023) found no effect of environmental unpredictability on reproductive seasonality. A recent modelling study similarly detected limited effects of environmental unpredictability on evolutionary transitions to nonseasonal breeding (Burtschell et al, 2023).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations